Tomistyczna «La Révolution Sexuelle» O. Adriano Olivy OP - Andrzejuk, Artur (Studia Theologica Varsaviensia, 2017)
In the Dominican reputable publishing ‘Cerf’ was published a book of father Adriano Oliva OP. The aim of this book is ‘pastoral’ reinterpretation of traditional teaching of the Church about second marriage of people who are divorced (les divorces remariés) and homosexual couples (les couples homosexuels). A. Oliva is basing his suggestions on texts of St. Thomas Aquinas. Father Oliva his considerations about marriage begins (p. 7) from quotation from Thomas’ Summa contra Gentiles where Thomas says that between husband and wife there is occured amicitia maxima (the largest friendship). The sign of amicitia maxima is not only sex life (actus carnalis copulae) but also the co- -existence in the household (domestica conversationis consortium). The analysis of ontological structure of marriage broadly is unanimous with the text of Aquinas but the consequences formulated from it are contradictory with his moral teaching about marriage and family. According to father Oliva the method of reinterpretation of Thomas’ teaching consists in separating one sentence from wider context and ‘commissioning’ its justifying conclusions. These conclusions are absolutely contradictory with Thomas Aquinas’ views which are voiced expressis verbis. Father Oliva uses this method also in respect of homosexsuality. The sentence quoted above about marriage’s friendship as the biggest friendship between people is in Thomas’ text one of the arguments for inseparably (indivisibilitas) of marriage and it is taken from chapter on the topic. Father Oliva takes a sentence from the text of the inseparably of marriage and in his book this inseparably is weakened in some way. Father Oliva used a statement of Thomas Aquinas’ – if a nature of some man is corrupted (natura corrupta), for this man it will be connaturale this what is contra nature (contra naturam). Thomas gives as examples cannibalism, bestiality and homosexuality. On the basis of that father Oliva writes that homosexuality being incompatible with the generally understood nature is natural for homosexual people because of their individual nature. Dominican scholar as if he had forgotten that the ‘individual nature is the result of corruption (corruptio). The way out of corruption is either repair or destruction the nature. Meanwhile father Oliva proposes the third way: the acceptance of corruption. In Thomas’ works we will not find basis for that acceptance. The book of Adriano Oliva, rather proclaimed in its views, are complete misunderstanding in the sense that it completely inaccurately selected basis for the proclaimed views. St. Thomas’ views are not good to justify to let to the Church’s sacraments divorces remariés and institutional acceptance of homosexual couples